Investigaciones cualitativas en salud publicadas en revistas biomédicas peruanas - Carcausto-Calla, Wilfredo Humberto (2018)
Introduction. In Peru, qualitative research in health with different characteristics has been carried out, although up to now there is no study regarding the status of the published documents. Our objective was to describe the characteristics of qualitative health research published in peruvian biomedical journals indexed in Latindex, SciELO Peru and Scopus during the years 2006-2016. Methods. Descriptive bibliometric study on qualitative publications in health. Results. Of the 67 original articles published, the annual production in the years 2006 to 2012 did not exceed 5 publications per year. As of 2013, there is a growing trend, with 2015 being the year of greatest production. 80,6% of the publications had as main authors the female gender, 19,4% received funding and 22,4% registered their research in ethics committee. The most studied discipline was care sciences and service with 53,7%. 41,8% of the qualitative designs were descriptive. Most of the articles were published in the journal “In Crescendo de Ciencias de la Salud”, “Anales de la Facultad de Medicina” and the “Revista Peruana de Medicina Experimental y Salud Publica”, with 19,4% (n=13), 17,9% (n=12) and 16,4% (n=11) respectively. Conclusions. Qualitative health research showed a growing trend in Peru. There have been more descriptive qualitative studies in the discipline of care and service sciences, the majority of articles had no funding or registration authorization by the ethics committee.